PENJADWALAN ULANG PEMBIAYAAN MIKRO MURĀBAḤAH DI BANK SYARIAH MANDIRI CABANG DUMAI PROVINSI RIAU - Ahmad Maulidizen; Mohammad Taqiuddin Bin Mohamad (Islam Futura, 2017)
This research is analyzing implementation of the rescheduling in Murābaḥah micro financing at Bank Shariah Mandiri, Indonesia. It was found that many Islamic banks in Indonesia are experiencing problems because of non-performing financing and can degrade the performance of the bank. Therefore, the bank implemented the rescheduling of non-performing Murābaḥah micro financing not to exceed a predetermined rate of Bank Indonesia at 5%. This research was conducted to find out more about the legal implementation of rescheduling in Murābaḥah micro financing at Bank Shariah Mandiri Branch Dumai. The reserach used data collection methods by observation, interview and library data then analyzed using the inductive, deductive and comparative. The research found that the implementation of rescheduling in Murābaḥah micro-financing at Bank Shariah Mandiri Branch Dumai is not fully in line with the Shariah because there is an Islamic ruling of Syariah National Board of Indonesia that have not been implemented, which the bank parties have been still burdening customers other than the actual cost.